The Hidden Language of Colors in Human Emotions - Dela Cruz, Ester; Jacinto, Eliza; Bonus, Jina; Gamas, Pedriluz Joy Love; Planco, Salome; Abaya, Florentino; Lim, Amparo; Malbas, Mylene; Ignacio, Mheliza Ann; De La Paz, Karen Michelle (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined how secondary school students associate common colors with selected emotional meanings and determined whether color preference is significantly associated with self-reported emotional state. It was anchored in the Color-in-Context perspective and the affective dimensions of valence and arousal, recognizing that color meanings are shaped by hue, brightness, saturation, personal experience, cultural interpretation, and environmental context. A descriptive-correlational research design was employed among 100 Grade 7 to Grade 10 students from a secondary school located in Barangay 311, Zone 31, Santa Cruz, Manila. The sample comprised 50 male and 50 female respondents selected from a population of 450 through stratified random sampling with equal allocation. Data were collected using a researcher-developed questionnaire covering demographic characteristics, multiple-response color–emotion associations, primary color preference, and self-reported emotional state. Frequency, percentage, and the chi-square test of independence were used to analyze the data. Blue was most strongly associated with calmness at 82%, black with sadness at 79%, yellow with happiness at 78%, red with excitement at 75% and anger at 68%, green with calmness or relaxation at 74%, orange with excitement at 70%, gray with sadness or boredom at 67%, white with calmness or clarity at 65%, and purple with calmness or creativity at 62%. The chi-square test indicated a statistically significant association between color preference and self-reported emotional state, with p = .021. However, the available statistical output did not establish the strength of the association. The study concludes that colors function as a recognizable but flexible language of emotion whose meanings vary according to visual, personal, cultural, and contextual factors. The findings support SDG 3 on Good Health and Well-Being and SDG 4 on Quality Education by providing evidence that may guide context-sensitive visual design in educational environments.
Keywords: Color–Emotion Association; Color Preference; Color Psychology; Emotional State; Learning Environment; Student Well-Being